γδ T Cells Cross-Link Innate and Adaptive Immunity in Mycobacterium tuberculosis Infection - Serena Meraviglia; Sary El Daker; Francesco Dieli; Federico Martini; Angelo Martino (Clinical and Developmental Immunology)
Protective immunity against mycobacterial infections such as Mycobacterium tuberculosis is mediated by interactions between specific T cells and activated antigen presenting cells. To date, many aspects of mycobacterial immunity have shown that innate cells could be the key elements that substantially may influence the subsequent adaptive host response. During the early phases of infection, innate lymphocyte subsets play a pivotal role in this context. Here we summarize the findings of recent investigations on γδ T lymphocytes and their role in tuberculosis immunity.